ANALISA POTENSI UNTUK PENGEMBANGAN INDUSTRI KULIT DI GUNUNG PUNTANG KABUPATEN BANDUNG - Dian Kurnianingrum; Iston Dwija Utama; Nur Azmi Karim; Chyntia Ika Ratnapuri (Faculty of Economics and Business, Universitas Malikussaleh, 2019)
Gunung Puntang in Bandung Regency West Java is known as one of a coffee and vegetable producer. Moreover, it is also wellknown as a leather craft industry center in West Java. Research entitled